The Georgian knot: The crisis in South Ossetia in the context of Georgian-Russian relations - Martina Bielawski; Uwe Halbach (Stiftung Wissenschaft und Politik (SWP), 2004)
The horrific act of terror that took place in the Russian republic of North Ossetia in the North Caucasus has pushed South Ossetia out of the international headlines. But the crisis in South Ossetia has not been overcome and still deserves attention. Since November 2003, international interest in developments in the South Caucasus and elsewhere in post-Soviet space has been determined by Georgia's political 'new beginning.' Initially the reform program of the young Georgian government under President Saakashvili aimed at combating problems such as corruption and strengthening the state stood in the forefront. The process of reviving the state in a country that previously served as an example of a failing state is being supported with substantial financial aid from external actors, including, the US, EU and the World Bank. (SWP Comments / SWP)
Keywords: 320